Measurement of different obstacles effect on rectangular cavity in low Reynolds number flow field using particle image velocimetry - Zahari @ Annuar, Ahsan Nur Mubarak (2013)
Flow past a cavity is a topic of great interest in the field of fluid dynamic properties. The characteristics of the flow depend on the Reynolds number, types of boundary layer, Mach number and the geometry of the cavity itself. Even though a large amount of investigation has been instigated for various objectives and aspects of the flow, the properties of dynamic flow involving cavities have yet to be fully discovered. Review of literature leads to the need of investigation about the effect of an obstacle in front of a rectangular cavity. The cavity can be explained as a two-dimensional body that would disturb the flow from upstream to downstream which mathematically defined as loss of forces in momentum equation. The lost forces can be described as drag which can give a significant effect in terms of flow dynamic problem. By introducing an obstacle, the idea is to control the flow from entering into the cavity which is the main reason of cavity drag creation. The purpose of this current experiment was to investigate the effect of six different types of obstacle at the leading edge of a rectangular cavity in upstream laminar flow condition with ReL = 5.12 x 104. The haracterization also included the changes of cavity depth with respect to cavity length (L/D = 4, 2.29, and 1.78) and freestream velocity within a very low speed region (V = 3.8 m/s, 4.8 m/s, and 6.5 m/s). The findings of this current experimental result will be used in the development of predicting fluid behaviour inside the cavity associated with this flow field. The experiment was conducted in an open subsonic wind tunnel designed purposely for low speed regions. The data was obtained by using 2-D Particle Image Velocimetry (PIV). The test model was designed using transparent materials for both flow visualization and allowing the laser sheet to pass through in experiments,acquiring 700 image pairs for each individual experiment resulting in an overall velocity vector. The result was produced using a mean velocity profile that was separated into u and v components. Analysis of the data showed that the obstacle affected the flow inside and above the cavity. Changing the obstacle type also changes the strength of vortex occurrence within the cavity with the triangle obstacle of 1 cm width and rectangular obstacle of 1 cm width generated the best flow behaviour among obstacles for differentiating the cavity depth and velocity within low Reynolds number region. The significance of result can be used as a foundation result for further investigation to any type of cavity with obstacles research.